Development of medical leadership competence during undergraduate medical students’ final year – a cross-sectional cohort study - Barbara Ogurek; Sigrid Harendza (BMC Medical Education)
Abstract Background Medical leadership plays an increasing role in quality healthcare. Nearly all physicians hold leadership roles during their career. Therefore, the development of medical leadership competence should start during undergraduate education and continue to postgraduate training. Some medical schools offer specific leadership programs, but in many medical schools, students are just embedded in the clinical environment, observing leaders in action. The goal of our cohort study was to explore how undergraduate medical students assess their leadership competences at the beginning and at the end of the final year without participation in a leadership program. Methods Between November 2023 and June 2024, we conducted a cross-sectional cohort study with 112 students at the beginning (1st trimester) and 117 students at the end (3rd trimester) of their final year. All participants assessed their leadership competence with the Medical Leadership Competence Scale (MeLeCoS) on a 5-point Likert scale (1: ‘never’, 2: ‘rarely’, 3: ‘sometimes’, 4: ‘often’, 5: ‘always’). A t-test and Mann-Whitney-U-tests were calculated for the overall MeLeCoS score, for the six MeLeCoS factors, and the 37 items, respectively, to test for significant differences between both cohorts. Within both cohorts, factors were ordered according to their mean values. Wilcoxon-tests were calculated to look for significant differences between two adjacent factors. Results No significant differences could be found between both cohorts for neither the overall MeLeCoS score nor for any of the factors or any item. In both cohorts, the factor 2 (‘Demonstrating responsible behaviour and shaping relations’) had the highest level in the self-assessment (1st trimester; 4.32 ± 0.40 and 3rd trimester; 4.31 ± 0.36). Factor 4 (‘Developing self-management and supporting management in healthcare’) and 6 (‘Introducing systemic perspectives into organizations’) were the only factors that showed no significant difference in their adjacent mean values. Conclusions Given that there were no significant differences between both cohorts, including teaching of medical leadership into the final year is recommended. As some medical leadership competences are highly developed at the beginning of the final year, a medical leadership curriculum should start before the final year. Individual development could be monitored and reflected by self-assessment using the MeLeCoS.